O Movimento Estudantil nos tempos da Barbárie: A luta dos Estudantes da UECE em defesa da Universidade Pública - Araújo, Raquel Dias (2006)
The research was developed within the Work and Education Section of the Graduate Program in Education of Federal University of Ceará (UFC), being, furthermore, associated to the investigative program of the Work, Education and Class Struggle Research Group of the Labor Movement Studies and Research Institute of Ceará State University (IMO/UECE). It intended to investigate the historical role performed by the student movement in defense of the public university, attempting, at the same time, to point out the main factors which account for the privatizacion and commercializacion of higher education in the last two decades, as well as the responses given by the student movement in general to such problem. The specific locus of the research was Ceará State University (UECE), and more particulary, its Pedagogy Course. The study was basead upon the marxist theoretical and methodological perspective, thus, attempting to establish the relationships between the public university tragedy and the deep, structural crisis of capital; as well as, to analyze the student movement in the context of class struggle. A thorough review of literature; an analysis of a consistent amount of documents; and open or/and semi-structured interviews applied to a number of current and former student leaders were the data collection procedures. The study drew an historical overview of UECE student movement, with greater emphansis put upon the actions undertaken in defense of public university, under the leadership of the Student Central Organization (DCE), throughout is fifteen administrative turns, and those put into effect by the Pedagogic Academic Centre (CA), in the course of its nineteen turns. The results of the study indicate that the student movement is not a thing of the past. In fact, it was brought back to life, in 2005, after nearly ten years of reflux, through a general strike, which was yet to take place at UECE, and was able to united students and labor unions in favor of the continued existence of public university.